Effect of the flood pulse on the ostracod assemblage (Ostracoda: Podocopida) in microenvironments in the Ciénaga Río Viejo, Colombia. - Ruiz-Jiménez, Jenny Alejandra (2023)
Introduction: Ciénagas are lowland tropical lakes in rivers floodplains, characterized by annual flood pulses, that modulate changes in biotic and abiotic variables. Biological assemblages have different responses to flood pulses, remaining either undisturbed or with significant changes in composition and abundance. Objective: Here we evaluate how ostracod species assemblages associated to macrophytes are modified throughout an annual flood pulse in Ciénaga Rio Viejo, Santander, Colombia. Methods: We used freshwater ostracods (bivalved microcrustaceans) as model group, because of its high sensitivity to environmental changes and high diversity in tropical systems. We sampled during four different hydrologic periods of the flood pulse: low, high, rising, and descending waters and at three stations were the flood pulse must have the most important effect (affluent and effluents) also, we take different physic-chemical parameters. Result: ACP analysis showed environmental fluctuations associated to flood pulse in the system. Three taxonomic families and six species were observed, out of which five species are new records for Colombia. The ANOSIM test showed no significant variations in the composition and abundance of the spatio-temporal ostracod assemblage, suggesting that assemblages are buffered against environmental changes driven by hydrological fluctuations, likely by their association with macrophytes. RDA shows (p-valor 0.078) that autochthonous species Strandesia cf. sphaeroidea and Keysercypria sp2 are more sensitivity to hydrological fluctuations than cosmopolites species. For Strandesia cf. sphaeroidea transparence were related of their occurrence during high waters and Keysercypria sp2 conductivity and pH were related of their occurrence during low waters. Conclusions: The new ostracod records for Colombia expands the distribution ranges of the species in South America. Flood pulses induced environmental changes in Cienega Rio Viejo, but macrophytes cover buffer ostracod assemblages variability. Generalist ostracod species were less disturbed than autochthonous species. This updated tropical freshwater dataset contributes towards filling the knowledge gaps related to habitat suitability of ostracods communities in Colombia.